TEKS ADIPARWA DALAM KAJIAN SOSIOLINGUISTIK: KONTAK BAHASA SANSKERTA DALAM BAHASA JAWA KUNA - Putu Eka Sura Adnyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The adjustment of the grammar system as a result of language contact can be seen in the literature in Old Javanese, namely the Adiparwa book. The Adiparwa book is a literary work in prose that is unique by using two languages, namely Old Javanese and Sanskrit sloka quotes. sociolinguistics and linguistics have the same research methods, both are always based on empirically collected results that are applied to data, and conclusions are drawn inductively. Language contact occurs at the grammatical level, where only the syntactic field includes the presence of phrases with a pattern of Sanskrit structures. d) vocabulary field found 363 types of use of Sanskrit vocabulary in the Adiparwa text. e) the semantic field includes cultural absorption (semantic expansive), the formation of new meanings (semantic additives), and changes in meaning values ​​(semantic replasive). The factors causing the integration of Sanskrit into Old Javanese in the Adiparwa text are two intralingual factors and extra lingual factors.